Значение клубеньковых бактерий люцерны и эспарцета в толще техноэкосистем - Узбек, Іван Харлампійович; Uzbek, Ivan; Волох, Петрo Вoлoдимирович; Volokh, Petro; Мицик, Oлександр Oлександрович; Mytsyk, Oleksandr (Дніпровський державний аграрно-економічний університет, 2015)
Встановлено, що в середовищі відпрацьованих кар’єрних територій зростають тільки ті види рослин, які володіють високою екологічною пластичністю своїх кореневих систем. Це бобові культури, насамперед люцерна і еспарцет, здатні фіксувати азот з атмосфери. Найбільша кількість бульбочок виявлена в насипному шарі грунтової маси. У червоно-бурих і сіро-зелених глинах бульбочки люцерни та еспарцету утворювалися здебільшого у верхньому 40-сантиметровому шарі порід (78–98 %). Підраховано, що корені люцерни спільно з бульбочковими бактеріями і вільноіснуючими азотфіксаторами щорічно можуть накопичувати в шарі 0–20 см близько 350 кг/га азоту. The development of the waste dump areas is difficult due to poor physico-chemical conditions of the tailings dumps. In this kind of environment grow and develop only those species that have a high ecological plasticity of their root systems. This legume crops, especially perennial forage legumes – alfalfa and sainfoin, can fix nitrogen from the atmosphere.Conducted studies to determine the number and weight of nodules in Medicago and Onobrychis. Peculiarities of formation of nodules depending on quality indicators moldboard mass.It is established that different ecotopes and create different conditions for the formation of nodules. Most of them were found in the bulk layer of the soil mass, where in the top one metre of this ecotope on one-dimensional plant 3rd year of life, on average, there were: 107–131 nodules of Onobrychis and 71–128 nodules – in Medicago.In red-brown and gray-green clay nodules of Medicago and Onobrychis was mostly formed only in the upper 40 cm layer in the race, where he majored 78–98 % of the nodules. All other things being equal, the number of nodules in Medicago was always less than that of the Onobrychis. With depth the nodules are small and Onobrychis, and at the 150–200 cm depth, they are practically absent.It is established that in nodules, living in the thick moldboard mass, contains 15–37 kg/ha of nitrogen, 4–7 kg of phosphorus, 6–8 kg of potassium and 15–35 kg/ha of calcium. It is estimated that the roots, such as Medicago, together with lubenko Vym bacteria and free-living nitrogen fixing bacteria can accumulate annually in the layer 0–20 cm on average about 350 kg of nitrogen per 1 ha.
Значення бульбочкових бактерій люцерни та еспарцету в товщі техноекосістем
Nodule bacteria of medicago and onobrychis the thick of technolgoical
Keywords: відвальна маса; dump mass; рекультивація; recultivation; екотоп; ecotope; бульбочки бактерій; nodules of bacteria